Chemical Threats in Thermally Processed Traditional Food and Possibilities of Their Reduction (Agricultural Engineering, 2019)
The objective of the paper is to review the present state of knowledge on health threats that occur as a result of some thermal processing of food products. Depending on the type and properties of raw materials and conditions of processes, carcinogenic, mutagen and genotoxic substances may be formed out of them, which may be treated as a process contamination. They are produced in processing plants, where their content is obligatorily controlled and organic, as well as in the conditions of food production in gastronomic units and households. The paper emphasises the second area of food processing, in particular, house-holds and popularised grilling processes, where there are no other possibilities of control of the threat level and awareness of people who prepare food and consumers is insufficient. The paper presents the most often occurring hazardous compounds, the most important regulations and admissible limits of consumption, as well as principles of thermal processing in a safe manner, and possibilities of limiting the levels of those substances in products.